Lymphomatoid papulosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Lymphomatoid papulosis is a clinically benign primary cutaneous T-cell lymphoma. Four infantile cases are described, the differences between children and adults are analyzed and the diagnostic difficulties are underlined. The most difficult differential diagnosis is with pityriasis lichenoides, which is characterized by a greater number of lesions and their eruptive monomorphism; on the other hand, the fluctuating trend with crops of new elements that is common to the two diseases has no importance, although in pityriasis lichenoides it is less evident for the greater number of lesions.